2010
DOI: 10.1002/ajhb.20998
|View full text |Cite
|
Sign up to set email alerts
|

Growth patterns in early childhood and final attained stature: Data from five birth cohorts from low‐ and middle‐income countries

Abstract: Growth failure is cumulative, and short stature is associated with multiple indices of reduced human capital. Few studies have been able to address in a single analysis both consideration of the timing of growth failure and comparison across populations. We analyzed data from birth cohorts in Brazil, Guatemala, India, the Philippines, and South Africa (n = 4,659). We used data on length at birth (available for three of the five cohorts), 12 mo, 24 mo, and mid-childhood to construct cohort- and sex- specific co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
150
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(168 citation statements)
references
References 22 publications
14
150
0
4
Order By: Relevance
“…Rapid weight gain in infancy (an increase in weight-for-age of greater than 0.67 Z scores between birth and 2 years [24]) was associated with greater skeletal maturity at age 9 years in both cohorts, despite their differing environments, with skeletal maturity advanced by the same magnitude in both settings; approximately 2.4 months per standard deviation score increase in weight from 0-2 years [13]. The conditional weight measure used here at 2 years, while not necessarily representing 'clinically significant' rapid infant weight gain, does represent the extent to which a child's rate of growth deviates from the rate predicted based on the individuals birthweight [14]. The finding that greater conditional weight at 2 years is positively associated with RSM at 9/10 years indicates that it is the tempo of growth in the first two years, rather than absolute weight at 2 years, which influences the rate of skeletal maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid weight gain in infancy (an increase in weight-for-age of greater than 0.67 Z scores between birth and 2 years [24]) was associated with greater skeletal maturity at age 9 years in both cohorts, despite their differing environments, with skeletal maturity advanced by the same magnitude in both settings; approximately 2.4 months per standard deviation score increase in weight from 0-2 years [13]. The conditional weight measure used here at 2 years, while not necessarily representing 'clinically significant' rapid infant weight gain, does represent the extent to which a child's rate of growth deviates from the rate predicted based on the individuals birthweight [14]. The finding that greater conditional weight at 2 years is positively associated with RSM at 9/10 years indicates that it is the tempo of growth in the first two years, rather than absolute weight at 2 years, which influences the rate of skeletal maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Separate models were built for each dimension of growth in order to ascertain the independent effects of weight and height on RSM, and also the effect of weight adjusted for height (BMI). To avoid the statistical issues associated with collinearity between measures at multiple time points within the same individual, conditional weight, height, and BMI variables at 2, 4 and 9/10 years were created to represent each individual's size given their previous size(s) [14]. Conditional measures represent the residuals from sex-specific regressions of weight Z-score (or length/BMI) on weight Zscores (or length/BMI) at all previous ages.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide patterns of linear growth faltering, based on data from many low-and middle-income countries (LMICs) (Victora and others 2010), indicate deterioration of child nutritional status, on average, from age 0 to 24 months; after this period, nutritional status levels off or slightly reverses (for example, Prentice and others 2013;Stein and others 2010). Analyses of the five countries in the Consortium of Health-Orientated Research in Transitioning Societies (COHORTS) study found that low birth weight or undernutrition at age two years (or both) were associated with shorter adult height, less schooling, and lower economic productivity (Victora and others 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Brain development occurs rapidly during this same period, from conception to age 2 years, laying the foundation for the development of cognitive, motor, and socioemotional skills throughout childhood and adulthood. The extent to which children globally are faltering in the development of these abilities during the first 2 years of life is less clear.…”
mentioning
confidence: 99%